2018
DOI: 10.2147/cmar.s160945
|View full text |Cite
|
Sign up to set email alerts
|

The miR-200 family: multiple effects on gliomas

Abstract: Gliomas are the most common type of primary brain tumors. MicroRNAs (miRNAs) are small noncoding RNAs that can epigenetically regulate target gene expression. The microRNA 200 family includes miR-200a, 200b, 200c, 141 and 429. Numerous studies have indicated that members of the miR-200 family play an important role in glioma development and metastasis. In this review, we summarize the data from various studies and highlight the effects of miR-200 on glioma metastasis, therapeutic response and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…41 The tumor suppressive role of miR-200 family is closely associated with the glinoma initiation, progression and metastasis. 42 These findings suggested the opposite function of miR-200a-3p and other miR-200 family members in cancers. In the present study, we found that miR-200a-3p was significantly upregulated in ovarian cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…41 The tumor suppressive role of miR-200 family is closely associated with the glinoma initiation, progression and metastasis. 42 These findings suggested the opposite function of miR-200a-3p and other miR-200 family members in cancers. In the present study, we found that miR-200a-3p was significantly upregulated in ovarian cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[9]. The miR-200 family members (miR-200a, miR-200b, miR-200c, miR-141, and miR-429) [10] could inhibite epithelial-mesenchymal transition (EMT) by targeting E-cadherin, ZEB1 or ZEB2 [11]. Interestingly, It was found ZEB1could bind to the promoter regions ofmiR-200b/200a/429 or miR-200c/141, suggesting that miR-200b could target inhibition of ZEB1 and control cell migration, invasion, and EMT [12].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse low-grade (WHO grade II) and III intermediate-grade gliomas are called lowergrade gliomas (LGGs) [4]. Because of their rapid growth and highly remarkable aggressiveness, a subset of these LGGs will develop into glioblastoma (WHO grade IV) within several months [5]. Glioblastoma (GBM) is the most common and malignant glioma, which is characterized by poor clinical prognosis and the survival time rarely exceeds 14 months [6].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, despite some remarkable achievements, the median survival time of glioma patients has not been signi cantly prolonged in the past decades [5]. There is still much room for research in the underlying pathogenesis, the multistep progression of glioma, and how to improve survival.…”
Section: Introductionmentioning
confidence: 99%